2017
DOI: 10.1515/jdis-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Digitizing Dunhuang Cultural Heritage: A User Evaluation of Mogao Cave Panorama Digital Library

Abstract: Purpose: This study is a user evaluation on the usability of the Mogao Cave Panorama Digital Library (DL), aiming to measure its effectiveness from the users' perspective and to propose suggestions for improvement.Design/methodology/approach: Usability tests were conducted based on a framework of evaluation criteria and a set of information seeking tasks designed for the Dunhuang cultural heritage, and interviews were conducted for soliciting in-depth opinions from participants. Findings:The results of the usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The comparison of quantitative results from the study by Hu et al (2017a) is also provided in Table 3, where the same evaluation framework was applied to evaluate the panorama collection of Mogao Cave. Results of Mann-Whitney U-test showed that visual appearance (p = 0.047), content (p = 0.006), and two-way communication (p < 0.001) showed significant improvement from user evaluation on the panorama collection.…”
Section: Quantitative Analysis Of Evaluation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of quantitative results from the study by Hu et al (2017a) is also provided in Table 3, where the same evaluation framework was applied to evaluate the panorama collection of Mogao Cave. Results of Mann-Whitney U-test showed that visual appearance (p = 0.047), content (p = 0.006), and two-way communication (p < 0.001) showed significant improvement from user evaluation on the panorama collection.…”
Section: Quantitative Analysis Of Evaluation Resultsmentioning
confidence: 99%
“…Afterward, the participants were individually interviewed with a set of open-ended questions on the basis of the criteria for sharing their experience and views in detail. This study followed the framework established in the study of evaluating the Mogao Cave panorama collection (Hu et al, 2017a), where a set of nine user tasks were designed specifically for Dunhuang heritage, ranging from simple factual tasks to more complex tasks involving comparisons and judgments (Appendix). An advantage of adopting this framework was to be able to compare the results to those in the study by Hu et al (2017a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were categorized into two groups: professionals (N 5 18) and the general public (N 5 12). The sample sizes are in line with previous studies on usercentered metadata evaluation, namely, 17 cultural heritage experts as interviewees in Amin et al (2008), 14 users in different groups in Hu et al (2017), and 33 survey respondents in Zhang and Li (2008). The group of professionals included researchers and scholars in related fields such as art history, Buddhist study, and ancient architecture, as well as those who had jobs related to cultural heritage, such as teachers, journalists, graphic designers, and cultural heritage librarians.…”
Section: Sample Selectionmentioning
confidence: 84%
“…Dunhuang Mogao Grottoes is the largest site of Buddhist art in the world, as well as world cultural heritage listed by the United Nations Educational, Scientific and Cultural Organization (UNESCO). The concept of digital Dunhuang was put forward in the 1990s, aiming for preserving and promoting the precious Dunhuang heritage using digital tools (Hu, Ho, & Qiao, ). Digital Dunhuang has successively implemented a series of projects, and a large number of digital resources have been built through data collection, processing, storage and management.…”
Section: Introductionmentioning
confidence: 99%